Comparison of efficacy of intralesional triamcinolone versus 308nm Excimer laser in the treatment of localized alopecia areata - Khan, Jahangir; Gul, Huma; Irfan Ullah; Khan, Mehran (Journal of Pakistan Association of Dermatologists, 2024)
Objective Â Comparison of efficacy of intralesional triamcinolone versus 308nm Excimer laser in the treatment of localized alopecia areata. Â Methods This study was done at dermatology unit Khyber teaching Hospital Peshawar, from 1st January 2023 to 30th June, 2023.All patients were allocated randomly into two groups by block randomization. Group A received 308 nm excimer laser twice weekly and group B got intralesional triamcinolone (10 mg/1ml) every three weeks. Patients were followed up at 12 weeks and mean SALT score at base line and follow up were documented. A response to treatment was labeled as effective if there was >75% hair growth (improvement) from baseline. Â Results As per calculated sample size, a total of 92 patients were equally divided into twoÂ groups, A and B, i.e. 46 patients in each group. Result analysis in our study showed that in group A, mean SALT score decreased from 15.44 at baseline to 5.42 at 12 weeks follow, with excimer Laser. Likewise, the mean SALT score in group B decreased from 14.64 at base line to a mean value of 6.35 at 12 week follow up with intralesional steroid treatment. From an efficacy point of view, group A showed an efficacy (>75% hair re-growth at 12 week follow up) of 56.5% while group B showed 67.4%. Â Conclusion Our study concludes that intralesional triamcinolone is more effective than 308 nm Excimer laser in the treatment of localized Alopecia areata. Â